2020
DOI: 10.1111/jfpp.14989
|View full text |Cite
|
Sign up to set email alerts
|

Novel postharvest intervention using rice bran wax edible coating for shelf‐life enhancement of Solanum lycopersicum fruit

Abstract: The edible coating is considered as one of the most-effective and safer ways to prolong the shelf-stability of the horticultural crops. Utilization of rice bran wax (RBW) as a coating substrate can be an excellent shelf-life extension strategy by transforming secondary by-product from rice processing into a useful coating substrate. This research was an attempt to use RBW as an edible coating and its effects on the shelflife extension of Marutham CO3 variety tomatoes. Crude RBW refined in laboratoryscale was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Respiration involves a series of biochemical changes, including enzymatic, oxidative, and reductive reactions, which are responsible for conversion of complex organic matter inside the cells into simpler substances in the presence of external oxygen giving out carbon dioxide and water along with production of heat (Mangraj and Goswami, 2011). The research have shown that continuing of respiration alone with the biosynthesis of ethylene inside the cells of tomato has a direct impact on the shelf‐life of tomato (Abhirami et al., 2020; Fitch‐Verges et al., 2019). During the climacteric phase, there is sudden increase in the cellular respiration along with outburst of ethylene production in a short interval of time, as shown in Figure 1, resulting in the dismantling of cell wall that leads to migration of moisture from inside of fruit to the outer environment and allowing the entry of oxygen inside, causing rapid senescence of the fruit.…”
Section: Overview Of Tomatomentioning
confidence: 99%
“…Respiration involves a series of biochemical changes, including enzymatic, oxidative, and reductive reactions, which are responsible for conversion of complex organic matter inside the cells into simpler substances in the presence of external oxygen giving out carbon dioxide and water along with production of heat (Mangraj and Goswami, 2011). The research have shown that continuing of respiration alone with the biosynthesis of ethylene inside the cells of tomato has a direct impact on the shelf‐life of tomato (Abhirami et al., 2020; Fitch‐Verges et al., 2019). During the climacteric phase, there is sudden increase in the cellular respiration along with outburst of ethylene production in a short interval of time, as shown in Figure 1, resulting in the dismantling of cell wall that leads to migration of moisture from inside of fruit to the outer environment and allowing the entry of oxygen inside, causing rapid senescence of the fruit.…”
Section: Overview Of Tomatomentioning
confidence: 99%
“…Rice bran wax‐coated tomatoes exhibited a decline of O 2 concentrations, but uncoated tomatoes showed a drastic reduction in O 2 . This might be due to high respiration rate in uncoated tomatoes, and rice bran wax coating slowed down the gas exchange (Abhirami et al ., 2020). The respiration rate of tomatoes coated with chitosan‐incorporated grape seed extract and stored at ambient temperature (25 °C) for 15 days was decreased compared with uncoated tomatoes (Won et al ., 2018).…”
Section: Effects Of Edible Coating On Respiration and Gas Exchange Of...mentioning
confidence: 99%
“…Edible coating from gum is one of biodegradable coating material which is highly available, simple to apply and less expensive compared to other means of preservation (Ruelas‐Chacon et al ., 2017; Thombare et al ., 2017) and it can be used to enhance shelf life of tomato. Edible coatings are considered as one of the most‐effective and safer ways to extend the shelf‐stability of the horticultural crops (Abhirami et al ., 2020). Edible coatings are non‐toxic, chemical free, residue free and chemically stable and sustainable substitute for conventional packaging materials (Ghadermazi et al ., 2019; Mohamed et al ., 2020).…”
Section: Advantages Of Using Edible Coatingmentioning
confidence: 99%
See 2 more Smart Citations